TRACER STUDY ALUMNI PRODI PENDIDIKAN ISLAM ANAK USIA DINI STAIN GAJAH PUTIH TAKENGON - Abdul Hafiz (Asosiasi Dosen Perguruan Tinggi Islam, 2020)
Abstract: This research is the result of tracer study alumni of Islamic Education programs for Early Childhood students at STAIN Gajah Putih Takengon, Aceh Tengah, Aceh. The need for tracer study data for alumni of study programs is needed to map the alumni existence and as an input for evaluating the internal quality of the study programs that have been implemented and taught to alumni. By using the census method, researchers took the entire PIAUD study program alumni, while the key informants in this study were 428 PIAUD Early Study alumni and graduate users. However, after conducting this research a total of 144 graduates were recorded. While supporting informants came from the head of the PIAUD study program, academic staff of STAIN GPA and other information. From this study it was revealed that graduates of the PIAUD study program had worked in various early childhood education institutions, such as being a TPA teacher, family planning teacher, kindergarten/RA teacher, civil servant, school principal, and school supervisor. And the average waiting period for them to get a job is less than one year. Keywords: Tracer Study, Alumni, Islamic Education programs for Early Chilhood Students Abstrak: Penelitian ini merupakan hasil tracer study alumni program studi Pendidikan Islam Anak usia Dini pada Sekolah Tinggi Agama Islam Takengon, Aceh Tengah, Aceh. Kebutuhan akan data tracer study Alumni Program Studi Pendidikan Islam Anak Usia Dini STAIN GPA sangat dibutuhkan untuk memetakan keberadaan alumni serta sebagai bahan masukan evaluasi terhadap mutu internal pelaksanaan program studi yang telah dijalankan dan diajarkan kepada alumni. Dengan menggunakan metode sensus, peneliti mengambil keseluruhan alumni prodi PIAUD, adapun yang menjadi informan kunci dalam penelitian ini adalah 428 alumni Prodi Pendidikan Islam Anak usia Dini dan pengguna lulusan. Namun setelah melakukan penelitian ini total lulusan yang terdata berjumlah 144 lulusan. Sementara informan pendukung berasal dari ketua prodi PIAUD, staf bagian akademik STAIN GPA dan informasi lainnya. Dari Penelitian ini terungkap bahwa lulusan prodi PIAUD telah bekerja di berbagai lembaga pendidikan anak usia dini. Mulai dari guru TPA, guru KB, guru TK/RA, PNS, kepala sekolah, maupun pengawas sekolah. Dan rata-rata masa tunggu mereka dalam mendapatkan pekerjaan kurang dari satu tahun. Kata Kunci: Tracer Study, Alumni, Mahasiswa Pendidikan Islam Anak Usia Dini